The effectiveness of visual learning methods: the definition of boundaries - N. A. Pervushina (Высшее образование в России)
At the article it’s posited the problem determining the boundaries of psychological approaches to the perception of visual information in the training. The possibility of combining different approaches in a single educational space is discussed on the methodological basis of information and synergetic conception of I.V. Melik-Gaykazyan. The article presents the results of the research project RFBR № 10-06-00313.